Flood risk management: implementation of the European Directive 2007/60/ec in the Autonomous Region of Madeira - Mileu, Nelson (2019)
The Decree-Law no. 115/2010, of October 22 transposed the Directive 2007/60/EC of the European Parliament and of the Council of 23 October 2007 on the assessment and management of flood risks into Portuguese national law establishing a framework for the assessment and management of flood risks. Flash floods and debris events have a long history in the island of Madeira resulting in several adverse impacts on human health, the environment, cultural heritage and economic activity. For this reason and since the catastrophic debris event of 20 February 2010 the establishment of a flood risk management plan in the Autonomous Region of Madeira (ARM) has assumed double importance. The aim of the paper is to present flood risk analysis methods and technical options adopted in the elaboration of flood hazard and flood risk maps as well the flood risk management plan strategy. The hydrographic basin of Socorridos is used as case study to show the principles and stages of the implementation of the Flood Risk Directive (FRD) in the ARM. In spite of some limitations associated with the volcanic mountain island characteristics and the debris events specificities, the flood risk analysis methods used are in harmony with the requirements of the FRD. Another important issue is the flood risk management plan strategy that addresses all aspects of flood risk management.